From Buddhist sati to Western mindfulness practice: A contextual analysis. Issue 1 (2nd January 2016) - Nilsson, Håkan; Kazemi, Ali
ABSTRACT: Over the last three decades, the practice of mindfulness has grown to become one of the most widespread health promoting applications in the West—so much that terms like yoga and meditation have now become standard household words. The purpose of this article is to discuss the meaning of mindfulness within both its Buddhist and its Western contexts. In the former case, the aim will be to shed light on mindfulness as a concept and practice that is rooted in Buddhist understandings (i.e., the Buddhist perspective); and in the latter case, the meaning of mindfulness will be more broadly explored in terms of its relevance to society, social work, and everyday life (i.e., the social [work] perspective).